2019
DOI: 10.15666/aeer/1702_27332743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Harvest Aiding Chemicals on Yield and Yield Components of Cotton (Gossypium Hirsutum L.)

Abstract: The effect of different harvest aiding chemicals on yield and yield components of cotton (Gossypium hirsutum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
1
1
Order By: Relevance
“…Özkan and Kaynak (2009) obtained the highest yields between 1-6 fruiting branches, which is compatible with our findings. In contrast to our study, the highest fiber yield per plant was reported between 4-9 fruiting branches by Jenkins et al (1990a), between 3-7 fruiting branches by Hake et al (1996), between 6-10 fruiting branches by Beyyavaş and Haliloğlu (2019). The effect of Sowing Date * Cultivars and Sowing Date * Boll Position interactions on fiber yield per plant was not significant, while other interactions were significant (P<0.01).…”
Section: Fiber Yield Per Plant (G)contrasting
confidence: 99%
See 2 more Smart Citations
“…Özkan and Kaynak (2009) obtained the highest yields between 1-6 fruiting branches, which is compatible with our findings. In contrast to our study, the highest fiber yield per plant was reported between 4-9 fruiting branches by Jenkins et al (1990a), between 3-7 fruiting branches by Hake et al (1996), between 6-10 fruiting branches by Beyyavaş and Haliloğlu (2019). The effect of Sowing Date * Cultivars and Sowing Date * Boll Position interactions on fiber yield per plant was not significant, while other interactions were significant (P<0.01).…”
Section: Fiber Yield Per Plant (G)contrasting
confidence: 99%
“…Zhao et al (2012) stated that the highest boll weight was recorded in the low positional sympodial branch (1-5 fruit branches) position, while Haliloğlu (1999) found that the boll weight per plant was higher in the uppermost part of the fruiting branches (11th-15th fruit branch). In contrast, Beyyavaş and Haliloğlu (2019) indicated that the position does not have a significant effect on boll weight.…”
Section: Boll Weight (G)mentioning
confidence: 85%
See 1 more Smart Citation
“…Ming-wei ve ark. ( 2013) tüm uygulamaların kontrol parsellerinden daha fazla koza açılmasına katkıda bulunduğunu; Beyyavaş (2019), hasada yardımcı kimyasal uygulamaların kontrole göre daha fazla açan koza oluşturduğunu belirtmeleri; Raghavendra ve Reddy (2020), yaprak dökücü uygulamadan 7 gün sonra, Dropp ultra 250 ml ha -1 'da (%92.3), Dropp ultra 200 ml ha -1 'da (%90.0) ve Ethrel 300 ml ha -1 (%89.0) oranında artış olduğunu belirtmesi çalışmamızla uyum içerisindedir.…”
Section: Uygulamadan 7 Gün Sonra Açan Koza Sayısıunclassified